Appraisal of fiber-metal laminate panels reinforced with metal pins deposited by CMT welding. (15th November 2017) - Skhabovskyi, Iaroslav; Batista, Natassia Lona; Damato, Cesar Augusto; Reis, Ruham Pablo; Botelho, Edson Cocchieri; Scotti, Américo
Abstract: Adhesion between metal and composite is key to fiber-metal laminates (FML). CMT (Cold Metal Transfer) welding has been used for hybrid joints that couple metal pin anchoring with adhesive bonding, but this concept has not been extended to FML panels yet. The objective of this work was to employ metal pins deposited by CMT PIN in FML panels. Panels with different pin deposition patterns were compared with panels without pins in terms of impact energy dissipation and damage characterization, and damage tolerance by means of compression and buckling tests after impact. The pins did not make the FML panels more brittle and the change in deposition pattern did not change the capacity to dissipate impact energy. The pins increased the maximum permanent deformation of the panels after impact, especially if less spaced. The in-plane damage areas were larger in the panels with pins, corroborating the damage depth profile results and their connection with impact energy dissipation. The compression and buckling tests indicated that the pins have potential to improve damage tolerance of FML panels, since a less-catastrophic behavior was observed. Pin anchoring seems to retard propagation of debonding between metal sheets and composite and hold back delamination within the composite.